EKSPLORASI POTENSI DAN BAKAT INDIVIDU SEBAGAI LANDASAN PENGEMBANGAN EKONOMI KREATIF - Farrel Deano Haryanto; Fedra Tryastami; Femi Mauliddia Amanda; Mudzakir (Abdi Jurnal Publikasi, 2026)
This Community Service Program (PKM) aims to enhance high school students’ understanding of individual potential and talents as a foundation for developing the creative economy. The main problem faced by the partner institution is the low level of students’ awareness of their personal potential and the suboptimal utilization of their talents as productive activities with economic value. The PKM activity was conducted at SMAIT An-Nawawi Al-Bantani using interactive counseling methods, group discussions, and self-reflection. The participants were students from grades X and XI. The results of the program indicate an improvement in students’ understanding of how to identify their individual potential and talents and their relationship with opportunities in the creative economy. Furthermore, the students demonstrated greater enthusiasm and motivation to develop their potential in a positive and productive way. This activity contributes to fostering a creative and innovative mindset among students as preparation for facing the challenges of the creative economy in the future.